SOUTHWESTERN COAST OF CHILE (PATAGONIA) CARTOGRAPHIC IMAGE AT XVI CENTURY - Martinic, B. Mateo (My University, 2023)
The evolution of the initial geographic knowledge of the southwestern coast of Chile, from the time of its invention until the end of the 16th century, with the vicissitudes of its cartographic recognition after overcoming the official secrecy imposed by the Hispanic monarchy to the news obtained after the first explorations.
Keywords: cartography; chilean southwestern coast; patagonia